Development and validation of a video on bed baths - Juliana de Lima Lopes; Rui Carlos Negrão Baptista; Tânia Arena Moreira Domingues; Rosali Isabel Barduchi Ohl; Alba Lucia Bottura Leite de Barros (Universidade de São Paulo, 2020)
Objective: develop and validate a video on bed bathing directed to nursing professionals and students. Method: the video was based on the literature and presents the definition of bed bath, indications for its performance, steps to perform it, and potential complications. Nursing professors and nurses validated it. They assessed the pertinence of content, clarity, and language of the video scenes. The Delphi Technique was used in this phase. After recording, three nursing professors, along with undergraduate nursing students from a public university, assessed the educational video. The professors first watched the video and suggested changes, and then the students watched the video after the changes were implemented. Results: six rounds were needed for experts to validate the video script using the Delphi Technique. After the video recording, undergraduate students considered the video of easy understanding. Conclusion: the video script was composed of four topics and was validated by experts after six rounds. The video was assessed by the professors and nursing undergraduate students, who considered the topics and the video as a whole as apprehensible. This study is expected to contribute to professional training and improvement of the knowledge and skills of nursing students.